Access to Maternal Health Care for Native Canadians on Reserves in Northern Canada - Beking, David M. (Université d'Ottawa | University of Ottawa, 2013)
The history of abuse and isolation of Native Canadian populations has created a gap in maternal health care, resulting in infant mortality rates (IMRs) of 12 per 1000 births for on-reserve populations compared to 5.8 per 1000 births for the general Canadian population. This discrepancy is deemed a population health issue, as Native Canadian people constitute roughly 3% of the Canadian population, but have infant mortality rates similar to other third world countries. Currently, there are multiple government and non-government organizations in charge of providing maternal health care for on-reserve populations. A lack of a unified communication system linking these organizations creates a gap in the delivery of services and compromises the prenatal care in Native Canadians. The current method of caring for high risk pregnancies on Northern Canadian reserves is to fly the mothers out of their home community to a hospital that is both far away from their families and completely foreign to them. This practice contrasts with the cultural norms of the Native Canadian population, where expecting women receive antenatal care from elder women within their community. New models of care, in which midwives are the primary providers of antenatal care within a given community, have recently been implemented in Northern Quebec and other isolated areas of Canada. The midwives work with women elders of the community to provide a full system of maternal care. These new models show great promise in improving our current system of maternal health care for Native Canadians by providing more efficient and accessible antenatal care while also incorporating cultural norms of the communities.
Keywords: maternal health; Native Canadians; Aboriginal reserves; prenatal programs; Aboriginal health